Predictive value of dermoscopy for the treatment of port‐wine stains with large spot 532 nm laser. Issue 7 (12th March 2019) - Kwiek, Bartłomiej; Rożalski, Michał; Sieczych, Julia; Paluch, Łukasz; Kowalewski, Cezary; Ambroziak, Marcin
Abstract : Objective: We wanted to evaluate dermoscopy as a tool to predict the efficacy of port‐wine stain (PWS) laser treatment. Study Design and Methods: Large spot 532 nm laser was used for the treatment of 67 PWS. Efficacy was assessed with an objective 3D digital imaging analysis. Dermoscopy images were taken before the treatment and analyzed semi quantitatively for features and patterns. Results: The following dermoscopic features: "superficial vessels, " "deep vessels, " "deep lakes, " "superficial lakes, " and "thick vessels total" were identified as positive determinants of maximal global clearance effect (GCEmax), whereas "thin long vessels, " "bright background total, " "whitish veil, " "white circles, " and "perifollicular erythema" were found to be negative determinants. Rapid response correlated positively with "superficial vessels, " "superficial lakes, " and "thick vessels total" scores and showed inverse correlations with "bright‐red background, " "bright background total, " "white circles, " "peacock eyes, " and "perifollicular erythema" scores. "Superficial vessels, " "thick vessels total, " and "pale‐pink patchy background" were predictors of the lack of response. Dominance of "deep vessels" was a predictor of 75% of responses and dominance of "brown areas" feature was the predictor of clearance. Patients responded to treatment differently, depending on the dermoscopic pattern of PWS. Conclusion: Dermoscopy may be useful to predict the response of PWS to laser treatment: its rapidity, the risk of no response, and 75% response and clearance. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.